Social Representations of the Jihadist : A Study of an Emerging Identity in Street Culture - Tutenges, Sébastien; Wästerfors, David; Hedlund, Anna ; 0000-0002-3185-125X (British Journal of Criminology, 2025)
Over the last two decades, the social identity of the jihadist has become a central part of street culture. Depictions of jihadists can be found in popular music, movies and media reports. Propaganda celebrating or condemning jihadism circulates online, and a significant number of individuals with a background in street crime have flirted with or converted to jihadism. Drawing on ethnographic fieldwork in Oslo, this article analyses how Muslims involved in street life and crime construct and relate to the social identity of the jihadist. The Durkheimian theory of representations is employed to show how the joint construction of this identity shapes the ways in which people on the street make sense of themselves, their enemies, and the actions they take towards jihadi extremism. In conclusion, we argue that the theory of representations, including the concepts of anchoring and objectification, should be incorporated into the analytical toolboxes of cultural criminology and narrative criminology to deepen our understanding of how meaning-making unfolds in cultural context.
Keywords: cultural criminology; Durkheim; jihadism; Moscovici; narrative criminology; social representations; street culture